Pengaruh Pemanfaatan Teknologi Informasi dan Sistem Pengendalian Intern terhadap Efektivitas Penatausahaan Aset Tetap (Studi Kasus pada Pemerintah Kabupaten Bandung Barat) - Triastiti, Mardila Suryandari; Suwondo, Sulistia (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The purpose of this study is to ascertain how internal control systems (SPI) and information technology (IT) use affect fixed asset administration efficiency. The Regional Work Unit (SKPD) in West Bandung Regency serves as the study's population. 56 respondents from 28 SKPD in the West Bandung Regency made up the study's sample. In this study, a descriptive verification technique with a quantitative approach was applied. Primary data were utilised as the data source. A questionnaire was used in the data gathering procedures. Multiple linear regression analysis is the technique utilised for data analysis. According to the study's findings, information technology does not significantly affect how well fixed asset administration works. Administration of fixed assets is somewhat impacted by the internal control system. While the efficiency of fixed asset management is simultaneously impacted by internal control systems and information technology.